Sources of Bias in Common Diagnosis of Chronic Inflammatory Bowel Diseases - O. A. Svatkova; A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Causal analysis of a late diagnosis of chronic inflammatory bowel diseases (CIBD) in general medical practice.Materials and methods. We continuously sampled 80 CIBD histories (44 of ulcerative colitis, UC, and 36 of Crohn’s disease, CD) to estimate the time and nature of first complaints, primary diagnosis, time lapse between the first physician visit and diagnosis and reasons for a late diagnosis.Results. Only 63.6 % of patients with UC and 38.9 % with Crohn’s disease were correctly diagnosed during the first visit and subsequent examination. Abdominal pain in debut of CIBD was registered in 40.9 % of the UC and 75.0 % of CD patients (p < 0.01). Diarrhoea as a CIBD manifestation was significantly more common in the UC than in CD patients (88.6 and 55.5 % of cases, respectively; p < 0.01). Hematochesia was observed in 68.2 % of the UC and 22.2 % of CD cases (p < 0.01). Among the CD patients with primary symptoms, a correct follow-up diagnosis was less frequent compared to the UC patients (38.9 % of cases, p < 0.01). Only 30 patients with UC (68.2 %) and 18 patients with CD (50.0 %) had colonoscopy at a first outpatient visit. The main cause of late diagnoses in CIBD is a delayed ileocolonoscopy.Conclusions. Ileocolonoscopy should be mandatory in all patients suspected for CIBD with clinical symptoms.